A Complete Guide to Maggot Therapy Clinical Practice, Therapeutic Principles, Production, Distribution, and Ethics - Stadler, Frank (Open Book Publishers, 2022)
Since the revival of maggot therapy in Western wound care approximately thirty years ago, there has been no comprehensive synthesis of what is known about its clinical practice, supply chain management, and social dimensions. This edited volume fills the information vacuum and, importantly, makes the current state of knowledge freely accessible. It is the first to provide sound, evidence-based information and guidance covering the entire supply chain from production to treatment. The chapters are arranged in five parts presenting the latest on clinical practice, the principles of therapeutic action, medicinal maggot production, distribution logistics, and the ethical dimensions of maggot therapy. The contributors have paid particular attention to the challenges encountered in compromised, low-resource healthcare settings such as disasters, conflict, and poverty. There are still many barriers to the widespread uptake of maggot therapy in healthcare settings. This book will be essential reading for a global audience of doctors, nurses, allied healthcare providers, students, and entrepreneurs with an interest in maggot-assisted wound care. It will be the go-to reference for those who plan, regulate, and coordinate healthcare, and want to establish a maggot therapy program, particularly in low- and middle-income and other compromised healthcare settings where maggot therapy can provide much-needed, affordable, and efficacious wound care.